The Efficacy of High-Volume Evacuators and Extraoral Vacuum Aspirators in Reducing Aerosol and Droplet in Ultrasonic Scaling Procedures during the COVID-19 Pandemic - Suwandi, Trijani; Nursolihati, Vidya; Sundjojo, Mikha; Widyarman, Armelia Sari (European Journal of Dentistry, 2022)
Objective SARS-CoV-2 can be carried by aerosols and droplets produced during dental procedures, particularly by the use of high-speed handpieces, air-water syringes, and ultrasonic scalers. High-volume evacuators (HVEs) and extraoral vacuum aspirators (EOVAs) reduce such particles. However, there is limited data on their efficacy. This study aimed to determine the efficacy of HVE and EOVA in reducing aerosols and droplets during ultrasonic scaling procedures.Materials and Methods Three ultrasonic scaling simulations were conducted on mannequins: 1. saliva ejector (SE) was used alone (control); 2. SE was used in combination with HVE; and 3. SE was used in combination with HVE and EOVA. Paper filters were placed on the operator's and assistant's face shields and bodies, and the contamination of aerosols and droplets was measured by counting blue spots on the paper filters.Statistical Analysis All data were analyzed for normality using the Kolmogorov–Smirnov test. The differences between each method were analyzed using a two-way ANOVA, followed by a posthoc test. The differences were considered statistically significant when p < 0.05.Result Using HVE and EOVA reduced aerosols and droplets better than using SE alone or SE and HVE: the posthoc test for contamination revealed a significant difference (p < 0.01). The assistant was subjected to greater contamination than the operator during all three ultrasonic scaling procedures.Conclusion The usage of HVE and EOVA significantly reduced aerosols and droplets compared with using SE solely. Using these techniques together could prevent the transmission of airborne disease during dental cleanings, especially COVID-19. Further studies of aerosol-reducing devices are still needed to ensure the safety of dental workers and patients.
Keywords: aerosol; droplet; extraoral vacuum aspirators; high-volume evacuators; ultrasonic scaling